Use of intravenous immunoglobulin for the treatment of autoimmune encephalitis: audit of the NHS experience - Kinsella, JA; Irani, SR; Hollingsworth, R; O’Shaughnessy, D; Kane, P; Foster, M; Schott, JM; Lunn, MP (SAGE Publications, 2018)
Objectives The treatments of limbic and other autoimmune encephalitis include immunosuppression, symptomatic treatment, and in the case of paraneoplastic syndromes, appropriate therapy for underlying neoplasms. When immunotherapy is considered, intravenous immunoglobulin is one option for treatment, either alone or in combination with corticosteroids. To date, however, evidence for the use of intravenous immunoglobulin in this context comes from case series/expert reviews as no controlled trials have been performed. We aimed to analyse the NHS England Database of intravenous immunoglobulin usage, which was designed to log use and guide procurement, to explore usage and therapeutic effect of intravenous immunoglobulin in autoimmune encephalitis in England.